Strength Analysis Due to the Elongation’s Ladder of Cutter Suction Dredger Ship - Hariyono Hariyono; Ganding Sitepu; Muhammad Zubair Muis Alie (EPI International Journal of Engineering, 2022)
The more frequent mining activities are carried out, the deeper the tin on the seabed, therefore many ship owners want to increase the length of the ladder on production suction vessels. The owner of the KIP Timah 8 suction boat will increase the length of the ladder to 70 meters, which previously was only 58 meters. The paper research are the response of the ladder structure before and after being extended, the limit strength of the ladder structure in the pulley area, then the ultimate strength of the longitudinal ladder structure due to the vertical bending moment. Lenght of the ladder construction subsequently increases commencing 58 m, 62 m, 66 m, to 70 m with each increase in length varying the slope angle of the ladder starting from 0o, 30o, 45o, to 60o. This paper uses a numerical method with the help of ansys software. The structure being reviewed is only in the ship ladder area. The response of the ladder structure before and after being extended, the maximum stress value occurs in the strut construction which is 49 meters from the ladder shaft, which is 56.88 N/mm2 and the maximum shift is 14.28 mm when the ladder length is 70 meters and still meets the allowable stress. Investigation of the limit strength using the Nonlinear Finite Element Analysis (NLFEA) method. Based on the results the analysis of the strength longitudinal ladder structure in the hogging and sagging conditions 42 meters from the ladder shaft, the maximum deflection in the column is 131.73 mm from the initial position before being loaded. While at an angle of 60 degrees it will collapse when deflection 66.17 mm. The results of the analysis showed that the load acting on the ladder the pipe load, cutter load and cutter torque the resulting stress still meets the stress that the longer ladder is directly proportional to the resulting stress and deflection value and the greater the slope of the ladder, the smaller stress and deflection.